Angiomatoid Spitz Nevus - Kwon, Oh Eon (Ann Dermatol, 2008)
Spitz nevus is a variant of melanocytic nevus which is histopathologically defined as large spindle and/or epithelioid cells. Angiomatoid Spitz nevus is a rare histologic variant of desmoplastic Spitz nevus characterized by prominent vasculature. We present a case of angiomatoid Spitz nevus, celluar type, that has not been reported before. We provide another example to show the remarkable diversity of Spitz nevus.